2018
DOI: 10.2139/ssrn.3273492
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Contribute: An Estimate of the Consequences of Non-and Underpayment of Self-Employment Taxes by Independent Contractors, and On-Demand Workers on Social Security

Abstract: is to produce first-class research and forge a strong link between the academic community and decision-makers in the public and private sectors around an issue of critical importance to the nation's future. To achieve this mission, the Center sponsors a wide variety of research projects, transmits new findings to a broad audience, trains new scholars, and broadens access to valuable data sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Or, in terms of price: A worker's Social Security benefits are a function of their lifetime earnings. However, independent contractors underreport their income in filing taxes (Bruckner and Hungerford 2021;Schreur and Veghte 2018), suppressing their future benefit. If the nontraditional type is a function of labor market barriers, then they by extension present a potential barrier to accessing Social Security or fully benefitting from it.…”
Section: Nontraditional Type As a Function Of Barriersmentioning
confidence: 99%
“…Or, in terms of price: A worker's Social Security benefits are a function of their lifetime earnings. However, independent contractors underreport their income in filing taxes (Bruckner and Hungerford 2021;Schreur and Veghte 2018), suppressing their future benefit. If the nontraditional type is a function of labor market barriers, then they by extension present a potential barrier to accessing Social Security or fully benefitting from it.…”
Section: Nontraditional Type As a Function Of Barriersmentioning
confidence: 99%
“…Findings from other countries confirm that the self-employed often underreport their earnings (Hurst, Li and Pugsley, 2010 [26] ; Bucci, 2019 [27] ). In the United States, a 2018 survey found that 32% of self-employed admittedly underreport their income for tax purposes (Bruckner and Hungerford, 2019 [28] ). Moreover, the inclination towards informality might be magnified when working with or through the internet platforms, especially if the platforms are based abroad and do not report any transaction data to Source: OECD domestic authorities.…”
Section: Income Validation Bargaining Power and Income Variabilitymentioning
confidence: 99%
“…A few countries introduced specific regulation to limit pension coverage gaps for selfemployed workers with only few major clients. While in Germany, self-employed persons who work predominantly for one client 28 and do not have employees have been mandatorily insured in the pension system since 1999, in Italy and Portugal the contributions of independent contractors relying on single contracts are now topped up by their clients. In addition, in Portugal if a self-employed worker depends significantly on one single client -the so-called ordering customer -the latter has to pay social security contributions for the self-employed.…”
Section: Policy Changesmentioning
confidence: 99%
“…European Commission (2018), "2018 Ageing Report; Economic and budgetary projections for the 28 A number of OECD countries achieved near-universal coverage of the working-age population through mandatory or quasi-mandatory plans in 2018. In ten OECD countries, voluntary private pensions (occupational and personal) covered more than 40% of the working-age population.…”
Section: Further Readingmentioning
confidence: 99%